1997
DOI: 10.1074/jbc.272.7.4444
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of GCV3, the Saccharomyces cerevisiae Gene Coding for the Glycine Cleavage System Hydrogen Carrier Protein

Abstract: YAL044, a gene on the left arm of Saccharomyces cerevisiae chromosome one, is shown to code for the Hprotein subunit of the multienzyme glycine cleavage system. The gene designation has therefore been changed to GCV3, reflecting its role in the glycine cleavage system. GCV3 encodes a 177-residue protein with a putative mitochondrial targeting signal at its amino terminus. Targeted gene replacement shows that GCV3 is not required for growth on minimal medium; however, it is essential when glycine serves as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 49 publications
0
35
0
Order By: Relevance
“…This may explain why in two standard Leishmania culture media the gcvP Ϫ mutant grew and differentiated normally. However, under conditions of excess glycine, growth of the gcvP Ϫ mutant was greatly inhibited (Table 2), as seen previously in plants or yeast (41,48,53). This may arise from the observation in other organisms that excess glycine contributes to decreased 5,10-CH 2 -THF production by SHMT (54), which would further reduce 5,10-CH 2 -THF levels in GCC-deficient mutants.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…This may explain why in two standard Leishmania culture media the gcvP Ϫ mutant grew and differentiated normally. However, under conditions of excess glycine, growth of the gcvP Ϫ mutant was greatly inhibited (Table 2), as seen previously in plants or yeast (41,48,53). This may arise from the observation in other organisms that excess glycine contributes to decreased 5,10-CH 2 -THF production by SHMT (54), which would further reduce 5,10-CH 2 -THF levels in GCC-deficient mutants.…”
Section: Discussionmentioning
confidence: 47%
“…We attempted to assay GCC activity enzymatically in crude and fractionated parasite extracts but were unsuccessful. In other non-photosynthetic organisms where glycine cleavage activity has been measured, it is very low; 0.1-0.2 nmol/min/mg of protein for yeast and E. coli (48). Thus, we devised an alternative indirect in vivo assay for GCC activity after incorporation of label from [2-14 C]glycine through 5,10-CH 2 -THF into thymidylate and then DNA (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Mutation in genes encoding a variety of cellular metabolic processes (supplemental Figure S6 at http://www.genetics. org/supplemental/) (Nagarajan and Storms 1997;Schneider et al 1997;Stoops et al 1997), such as the conversion of pyruvate into acetyl-CoA by pyruvate dehydrogenase complex (Pdx1p, Lpd1, Pdb1p, and Lat1p), the conversion of acetyl-CoA to malonyl-CoA by Hfa1p, fatty acid synthesis by fatty acid synthase complex (Oar1p, Mct1p, and Etr1p), glycine degradation (Gcv2p, Gcv3p, and Lpd1p), and a peptidase activity (Prd1p), resulted in a decrease of dipeptide utilization (Table 3). In these mutants the impairment of the dipeptide utilization appeared to be independent of Ptr2p transport activity since Ptr2p-GFP could be observed at the plasma membrane (supplemental Figure S3 at http://www.genetics.org/supplemental/).…”
Section: Gene Namementioning
confidence: 99%
“…The fourth subunit, lipoamide dehydrogenase, is present in several other multienzyme complexes (11). These genes are up-regulated following addition of glycine to the medium (12)(13)(14) via a glycine response element with the consensus sequence CATCN 7 CTTCTT (15). Previously, it was demonstrated that this glycine effect is a response to a decrease in cytosolic 5,10-CH 2 -H 4 folate levels rather than directly to glycine (16).…”
mentioning
confidence: 99%